Efektivitas Game Edukasi “Mahameru Saga” dalam Meningkatkan Literasi Mitigasi Erupsi Gunung Semeru pada Siswa MTsN 6 Malang - Hamim Thohari Mahfudhillah; Nayla Ramadhani Amanullah; Nabila Aisyah Paramitha; Neni Naqiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mount Semeru is an active volcano in East Java that poses eruption risks to surrounding communities. This situation necessitates strengthening disaster mitigation literacy through interactive and contextual learning. This study aimed to evaluate the effectiveness of the educational game "Mahameru Saga"—a 3D adventure game integrating the Mahameru legend with eruption mitigation content—in improving eruption mitigation literacy among 7th-grade students at MTsN 6 Malang. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The study subjects consisted of 36 7th-grade students selected as the trial sample. Data were collected via multiple-choice tests administered before and after using the game and were analyzed using quantitative descriptive methods, specifically the Normalized Gain (N-Gain). The results showed that the average pretest score of 60 rose to 76 in the posttest, representing a 16-point increase. The N-Gain of 0.40 fell into the "medium" category. These findings indicate an improvement in eruption mitigation literacy following the use of Mahameru Saga. Thus, Mahameru Saga demonstrates potential as an effective learning medium to support the enhancement of students' eruption mitigation literacy. However, further research involving larger sample sizes and an experimental design that includes a control group is required to obtain more robust evidence of its effectiveness.